MORPHOMETRY OF INTESTINAL LYMPHOID TISSUE IN EXPERIMENTAL PULMONARY FIBROSIS IN RATS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article reveals morphological changes in lymphoid structures of the rectal wall of mongrel rats with experimental pneumosclerosis. The study of the immune status of rats against the background of prolonged hypoxia in experimental pneumosclerosis revealed significant violations in the form of a sharp decrease in the number of lymphocytes. This served as a basis for comparative analysis of various morphological changes in lymphoid tissue and dynamics in rats, and also allowed to determine structural changes in intestinal tissues.